African inland fisheries - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
A strategic assessment of warm-water fish farming potential in Africa by J M Kapelsky 1994 CIFA Technical Paper 27 67pp ISBN 92 5 1036152